IMPLEMENTASI SAMPAH CERDAS DI UNIVERSITAS: SEBUAH SYSTEMATIC LITERATURE REVIEW - Effendy, Vina Ardelia; Sulasno, Mitsal Shafiq (Infotech: Journal of Technology Information, 2025)
The problem of waste management in DKI Jakarta is a major challenge for the local government, especially with the increase in waste generation which reaches an average of 41,079,420.38 tonnes per year and 112,546.36 tonnes per day by 2023. The limited management capacity means that around 30 tonnes of waste, or 16,286,946 tonnes, are not optimally handled. Waste management in the DKI Jakarta area is classified into household waste, household-like waste, and specific waste, which covers various sectors, including offices, universities, and public facilities. Universities have an important role to play in promoting environmental sustainability through the implementation of smart waste management concepts. This study aims to explore the application of an effective waste management system in an academic environment, as well as to provide comprehensive insights into research trends in the field of solid waste management. This study uses the application of a Systematic Literature Review (SLR) which is expected to provide insights into the application of smart waste management from various developed countries in the scope of Higher Education in the future and to support the implementation of sustainable waste management practices in Higher Education. By reviewing existing literature, this research also contributes to enriching academic understanding and empowering communities and stakeholders to realise more efficient and sustainable waste management systems. The results of this research are expected to provide insights for the academic world and the application of smart waste. In addition, the findings obtained can form the basis for further research to enrich understanding and the development of innovative solutions in this field.